Peran Psikologi Manajemen dalam Praktik Kepemimpinan Organisasi: Systematic Literature Review - Ahmadi .; Lely Anggraini; Dwi Ayu Hamdana; Mu' alimin (CV. ITTC INDONESIA, 2026)
The increasing complexity of educational organizations requires a management approach that not only focuses on administrative aspects but also considers individual psychological factors within the organization. Management psychology is an important approach in understanding behavior, motivation, and decision-making processes that influence organizational performance. Therefore, studying the role of management psychology in leadership practices and educational organization management is relevant to be examined systematically. This study aims to analyze the role of management psychology in improving leadership effectiveness, work motivation, and organizational performance based on previous research findings. The method used is a literature review by searching for scientific articles through Google Scholar using keywords related to management psychology, leadership, and organizational performance. The collected articles were then selected based on topic relevance, year of publication, and research suitability for further analysis. The results indicate that the literature on management psychology in educational organizations highlights three main themes: the role of motivation in improving individual performance, the influence of leadership in creating a positive organizational climate, and the contribution of management psychology in decision-making and problem-solving processes. These findings show that integrating psychological approaches into organizational management can enhance leadership effectiveness and organizational performance. Future research is recommended to examine empirical implementation across various educational institution contexts.